2003
DOI: 10.1257/089533003321164958
|View full text |Cite
|
Sign up to set email alerts
|

The Efficient Market Hypothesis and Its Critics

Abstract: Revolutions often spawn counterrevolutions and the efficient market hypothesis in finance is no exception. The intellectual dominance of the efficient-market revolution has more been challenged by economists who stress psychological and behaviorial elements of stock-price determination and by econometricians who argue that stock returns are, to a considerable extent, predictable. This survey examines the attacks on the efficient market hypothesis and the relationship between predictability and efficiency. I co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
672
0
63

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,434 publications
(833 citation statements)
references
References 35 publications
19
672
0
63
Order By: Relevance
“…Indeed, this is a minimal requirement for any predictive market model (see [Malkiel 2003]). In [Cross et al 2007] it was shown that there is no statistically significant difference between the the investment performance of agents with differing herding propensities C i (and hence nothing to be gained by adaptively changing their reaction to herding).…”
Section: B Rational Expectations and Efficient Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this is a minimal requirement for any predictive market model (see [Malkiel 2003]). In [Cross et al 2007] it was shown that there is no statistically significant difference between the the investment performance of agents with differing herding propensities C i (and hence nothing to be gained by adaptively changing their reaction to herding).…”
Section: B Rational Expectations and Efficient Marketsmentioning
confidence: 99%
“…We have demonstrated that boom-bust dynamics is one possibility that arises naturally and robustly without requiring any exogenous cause. However, 31 There is no clear consensus as to whether technical trading actually produces excess profits [Brock, Lakonishok and LeBaron 1992, Chan, Jegadeesh and Lakonishok 1996, Malkiel 2003 but if some strategies do indeed work then another interesting question is why? It may be caused by the presence of one or more systemic deviations from full rationality or it may in fact be a selffulfilling prophesy caused by sufficient numbers of technical traders using that rule themselves.…”
Section: Implications and Concluding Remarksmentioning
confidence: 99%
“…Therefore, the found predictability could be attributed to the intervention of the big traders at specific (yet unknown) threshold values. The EMH is confirmed whenever apparently profitable trading strategies are ruled out by market friction (Malkiel, 2003), in other words, some statistically significant anomalies are not economically significant. If the level of transaction costs needed to generate profits from an anomaly (therefore, eliminating it) is far below the level that actually exists in the market, it could explain why a reasonably efficient market allows the anomaly to exist (Wu and Shafer 2007).…”
Section: Discussionmentioning
confidence: 86%
“…The conventional study on the market efficiency hypothesis focuses on whether stock markets are of weak, semi-strong, or strong form efficiency. The empirical evidence has been mixed (Fama, 1970(Fama, & 1998Malkiel, 2003). This study contributes to the market efficiency literature by looking at whether a stock market becomes more efficient in a long-run in terms of a measure of market information asymmetry-the average discount rate for all firms in the market.…”
Section: Introductionmentioning
confidence: 99%